(untitled) (Economic studies journal, 2023)
This study aims to identify the strategies practiced by the human resources management in the Libyan manufacturing companies to keep pace with the recent changes in technology, and also to identify the method in which the process of providing training (training methods, training providers, training duration, training evaluation methods) to deal with these technological changes. The study population consisted of all manufacturing companies registered in the Libyan Ministry of Industry, which constitute a total of (110) large, medium and small manufacturing company. The results of the study indicate that the most used strategies that have been applied by those responsible for human resources management in the companies under study are new job description and now job design, as strategies used to keep pace with the introduction of new technology in these companies. The study showed that among the training methods used because of the introduction of new technology did the manufacturing companies under study to deal with technological changes as they happen use On-the-job training. The results of the study also revealed that there are statistic significant differences between the companies in terms of their size, when they use of-the-job training mothed as well as in terms of the nature of the training providers, as well as in terms of the training evaluation methods used by the companies under study, and also indicated that there are no significant differences statistics on the training duration, in terms of the size of the companies. The study recommended that more attention to human resources management to ensure achieving the highest possible level of performance for the companies under study, which reflected in providing quality services to clients.